ANALISIS PELAKSANAAN SISTEM JENJANG KARIR PERAWAT DI RS SWASTA KOTA TASIKMALAYA DAN RS PEMERINTAH KAB. CIAMIS - Fitri Nurlina; Nanan Sekarwana; Irman Somantri (Program Studi Keperawatan Universitas Muhammadiyah Tasikmalaya, 2021)
The nurse career ladder is one of the systems done by the hospital in order to improve the nurses’ performance and professionalism according to their expertise and also it can improve hospital’s service quality. The private hospital in tasikmalaya city and the government hospital in ciamis are tried to organize their system in order to improve the hospital’s service quality. This research aims to knowing the implementation the system in both of the hospitals. The research employs qualitative method and case study approach with eight participants netted by purposive sampling technique. The theme found is: 1) the reason of both hospitals implemented system; 2) differenced perception and effectiveness of role, function, and duties nurse department, nurse committee and training personnel; 3) availability of human resources implemented system; 4) optimization implemented system. The results found is differented perception of roles, functions, and duties between nursing department and committee, lacked of support and freedom of training personnel, nursing committee does not had subcommittee credentials, imbalanced proportion between number assessors and nurses and their workload, uncleared legality of implementation system from the director, inappropriated implementation since the system was previously done by the midwives, lacked of support and motivation, differented implementation between action and the actual rules as it was adjusted to the hospitals’ environment. It can be concluded that the implementation system was not yet optimal. The hospital should be able to support and plan the program is well. Pay more attention to requisite and facilities needed for implementation system, and propose the better appreciation to nurse in according to competence.